Ekstrak daun mangrove (A.marina)mempercepat kesembuhanulkus traumatikus (Extract of mangrove leaf (A.marina) accelerates the healing of traumatic ulcer) - Arvian Novanolo Mendrofa; Isidora Karsini S; Dian Mulawarmanti (Journal of Dentomaxillofacial Science, 2015)
Mangrove leaf (Avicennia marina) has a role in wound healing process, but its effect in wound healing in oral mucosa has not been researched yet. This study aimed to prove the effect of A.marina extract against traumatic ulcer and itseffective concentration in traumatic ulcer healing. The subjects of this research are 25 wistar rats that were randomized into 5 different groups; K0 control, K1 were given hyaluronic acid, P1 were given extract of A.marina10%, P2 were given extract of A.marina 20%, and P3 were given extract of A.marina 40%. After the subjects werewounded using amalgam stopper that has been heated before, they were given topical application once daily untilseven days. The ulcer diameter was measured at the second day and day 8 using caliper digital. The data, analyzedusing Kruskal-Wallis test showed that there’s difference in diameters between two groups (p<0.05). The averagediameter differences of traumatic ulcer among rats are K0 = 0.5700 mm, K1 = 0.8380 mm, P1 = 0.7240 mm, P2 =0.8440 mm, and P3 = 0.9500 mm. It was concluded that A.marina extract of 10%, 20% and 40% concentrations haveeffect in the healing of traumatic ulcer, and 40% is the most effective concentration against traumatic ulcer.